Pengaruh Leverage dan Arus Kas Operasi terhadap Financial Distress dengan Moderasi Profitabilitas - Fatimah Azzahra; Eli Safrida; Anggiat Situngkir; Ilham Hidayah Napitupulu; Putri Syuhada (Owner : Riset dan Jurnal Akuntansi, 2025)
The Indonesian textile industry faces intense competition and pressure from imported products, increasing the risk of financial distress. Financial distress, defined as the inability to meet financial obligations, threatens business continuity and is a major concern for investors and creditors. Prior studies on leverage, operating cash flow, and profitability show inconsistent results, leaving a gap in understanding, particularly regarding the moderating role of profitability. This study examines the effects of leverage and operating cash flow on financial distress and tests the moderating role of profitability in textile companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. Leverage is measured by the Debt to Equity Ratio (DER), operating cash flow by the Operating Cash Flow Ratio (OCF), and profitability by Return on Assets (ROA). Financial distress is identified using the Springate model, with scores below 0.862 indicating distress. Logistic regression with panel data was applied to 10 purposively selected companies, yielding 50 firm-year observations. The findings reveal that leverage significantly affects financial distress, while operating cash flow and profitability show no significant influence. Moreover, profitability does not moderate the effects of leverage or operating cash flow on distress. Theoretically, this study contributes to the Pecking Order Theory by highlighting the limited role of profitability as an internal financing source. Practically, it provides insights for managers, investors, and creditors to strengthen financial sustainability through better capital structure management and profitability improvement.